EVALUATION OF ENHANCED SOLAR DESALINATION SYSTEM PROTOTYPE - Rofiq Iqbal; Daffa Reyhan Aldrien Putra; Nur Novilina Arifianingsih; Dhimas Dwinandha (Universitas Trisakti, 2024)
Solar desalination technology has been one of the effective solutions to tackle the problem of water scarcity. A number of studies have been conducted at our water research group to determine which variable influences the quantity of distilled water produced by an independent solar desalination unit. Aims: This study was aimed to design and optimize a novel solar desalination unit and field-tested using the best variable from the previous studies. Methodology and results: Variables used from the previous studies were evaluated to obtain the best values for each parameter, those are: glass cover inclination, gap distance between water and glass cover, insulation thickness, water depth, and water mass flow rate. Those best values were then implemented in the optimized basin design, delivery mechanisms, evaporation techniques, and heat isolation methods. The optimized design can generate up to 2,778.2 mL/m2/8hrs of distilled water with an efficiency of 23.35% in preliminary test, and was field tested at Batukaras Beach, where it produced up to 902 mL/m2/8hrs with an efficiency of 13.56%. Conclusion, significance and impact study: Meteorological parameters and environmental conditions are important factors that greatly affect the performance and productivity of the desalination unit. The relative humidity is inversely proportional to the volume of distillate water, where the smaller the value, the greater the amount of distillate water that can be produced, and it has significant impact on the productivity of the prototype. The quality of the distillate water produced still needs improvement on the parameters of pH, turbidity, and total coliform.